Analysis Of Critical Thinking Dimensions In The Picture Story Atane Buja (Farming Salt) - Hardiansyah, Framz; Qomariyah, Aisyatul; Armiyati, Adinda; Rosalia, Amanda; Mustaf, Rifqy Qalib (Journal of Practice Learning and Educational Development, 2026)
This article examines children's illustrated stories as a literary work that has the potential to instill character values in the midst of the condition of children who experience obstacles in processing information properly, building relationships between various information, analyzing information, evaluating, and concluding it. The character value in question is the value of the Pancasila student profile, especially in the critical reasoning dimension. This study aims to determine the value of the critical reasoning dimension contained in the illustrated story of a Madurese child "Atane Buja". An analytical descriptive qualitative approach is used in this study. The children's illustrated story "Atane Buja" by Baytil Qudsiyah is the main source of research data that can be accessed through the website of the Ministry of Education and Culture, Research and Technology. The findings of the research, in the form of excerpts from the story of Atane Buja, are presented with a table. The results of this study show that the elements of acquiring and processing information and ideas, analyzing and evaluating reasoning, reflecting and evaluating their own thoughts are contained in the pictorial story of Atane Buja's child which can be adapted to events in students' lives. This children's illustrated story can be used as an effective learning medium in the formation and development of the character of elementary school students, especially in the critical reasoning aspect.